The Making of Wellbeing Measurement:: A (Kind of) Study Protocol - Simovska, Venka; O'Toole, Catriona (Outlines. Critical Practice Studies, 2021)
In this paper, we propose a ‘study protocol’ for researching the becomings of the Danish national wellbeing survey for schools. We engage with the idea of a published research protocol that originates from positivist research paradigms and medical research in particular. Within these paradigms, protocol serves the purpose of ensuring the objectivity and replicability of the research in question, and provides a sense of security to the researcher in terms of the quality of the research design. In contrast, with ideas of transmethodology in mind, we suggest a protocol that endeavours to support researchers to engage with ambiguity, uncertainty and singularity in research while still being attentive to quality. We suggest a protocol that helps de-stabilize the concept of wellbeing in schools and looks at how wellbeing as an object of measurement is (re)configured, who the human and non-human actors involved are, and what effects their assembling produces. These questions require research practices that acknowledge the complexities of the human condition and the richness of the social and material world. Instead of suggesting a “paradigm shift”, we are inspired by Patti Lather, who argues for a proliferation of paradigms, where proliferation refers to forming a pattern of interference. In other words, proliferation calls for reflection on the inconsistencies, confusion, disorganization of the research process, and both our need and caution to position ourselves epistemologically and ontologically. The protocol we suggest deploys diverse, sometimes complementary, sometimes contrasting methods, analytical strategies or theoretical perspectives in order to explore the problem at hand and engage with the ironies, tensions and uncertainties inherent to research.